A New Printable Alginate/Hyaluronic Acid/Gelatin Hydrogel Suitable for Biofabrication of In Vitro and In Vivo Metastatic Melanoma Models - Schmid, Rafael; Schmidt, Sonja; Detsch, Rainer; Horder, Hannes; Blunk, Torsten; Schrüfer, Stefan; Schubert, Dirk W.; Fischer, Lena; Thievessen, Ingo; Heltmann-Meyer, Stefanie; Steiner, Dominik; Schneidereit, Dominik; et al. (Advanced Functional Materials, 2022)
Two-dimensional (2D) cancer models have been the standard for drug development over the past few years, but they frequently do not resemble in vivo properties adequately. 3D models are superior in many aspects and are, therefore, more similar to human pathophysiology. Over the past years, the emerging field of biofabrication has made significant advances, resulting in even more sophisticated 3D models. With this study, a hydrogel is created for biofabrication that is suitable for mimicking the tumor microenvironment in vitro and is further tested as a new vascularized melanoma model in vivo. The alginate/hyaluronic acid/gelatin bioink shows good shape-fidelity, high cell survival rates, and enables successful cultivation of melanoma cells and adipose-derived stem cells as well as cell differentiation in vitro. In vivo, in the arteriovenous loop model, it proves to be a unique method to study melanoma progression, tumor vascularization, and ultimately and reliably metastases in an isolated and controlled environment. These results show that this 3D model is very application-oriented for molecular research and therapy development.
CRIS-Team Scopus Importer:2021-10-22
Keywords: bioinks; metastasis; stem cells; tissue engineering; tumors

A vascularized in vivo melanoma model suitable for metastasis research of different tumor stages using fundamentally different bioinks - Schmid, Rafael; Schmidt, Sonja; Schrüfer, Stefan; Schubert, Dirk W.; Heltmann-Meyer, Stefanie; Schicht, Martin; Paulsen, Friedrich; Horch, Raymund E.; Boßerhoff, Anja Katrin; Kengelbach-Weigand, Annika; Arkudas, Andreas (Materials Today Bio, 2024)
Although 2D cancer models have been the standard for drug development, they don't resemble in vivo properties adequately. 3D models can potentially overcome this. Bioprinting is a promising technique for more refined models to investigate central processes in tumor development such as proliferation, dormancy or metastasis. We aimed to analyze bioinks, which could mimic these different tumor stages in a cast vascularized arteriovenous loop melanoma model in vivo. It has the advantage to be a closed system with a defined microenvironment, supplied only with one vessel—ideal for metastasis research. Tested bioinks showed significant differences in composition, printability, stiffness and microscopic pore structure, which led to different tumor stages (Matrigel and Alg/HA/Gel for progression, Cellink Bioink for dormancy) and resulted in different primary tumor growth (Matrigel significantly higher than Cellink Bioink). Light-sheet fluorescence microscopy revealed differences in vascularization and hemorrhages with no additional vessels found in Cellink Bioink. Histologically, typical human melanoma with different stages was demonstrated. HMB-45-positive tumors in progression inks were infiltrated by macrophages (CD163), highly proliferative (Ki67) and metastatic (MITF/BRN2, ATX, MMP3). Stainings of lymph nodes revealed metastases even without significant primary tumor growth in Cellink Bioink. This model can be used to study tumor pathology and metastasis of different tumor stages and therapi
Keywords: Tissue engineering; Bioink; Melanoma; Tumor; Metastasis

Biofunctionalization of ADA-GEL Hydrogels Based on the Degree of Cross-Linking and Polymer Concentration Improves Angiogenesis - Heltmann-Meyer, Stefanie; Detsch, Rainer; Hazur, Jonas; Kling, Lasse; Pechmann, Sabrina; Kolan, Rajkumar Reddy; Osterloh, Justus; Boccaccini, Aldo R.; Christiansen, Silke; Geppert, Carol-Immanuel; Arkudas, Andreas; Horch, Raymund E.; et al. (Advanced Healthcare Materials, 2025)
The creation of bioartificial tissues is a promising option for the reconstruction of large-volume defects. The vascularization of tissue engineering constructs, as well as the material properties of the carrier matrix, are important factors for successful clinical application. In this regard, hydrogels are promising biomaterials, providing an extracellular matrix-like milieu that enables the possibility of cell transplantation and de novo tissue formation. Furthermore, biofunctionalization allows for a certain fine-tuning of angiogenic properties. This study aims to investigate vascularization and tissue formation of highly cross-linked alginate dialdehyde (ADA) and gelatin (GEL). This highly cross-linked network is created using a dural cross-linking mechanism combining ionic (Ca2+ ions) and enzymatic (human transglutaminase (hTG)) cross-linking, resulting in reduced swelling and moderate degradation rates. Vascularization of the ADA-GEL-hTG constructs is induced surgically using arteriovenous (AV) loops. Biocompatibility, tissue formation, and vascularization are analyzed by histology and X-ray microscopy. After only 2 weeks, vascularization of the ADA-GEL-hTG constructs is already present. After 4 weeks, both de novo tissue formation and vascularization of the ADA-GEL-hTG matrix increase. In conclusion, ADA-GEL-hTG-based hydrogels are shown to be promising scaffold materials for tissue engineering applications.
CRIS-Team Scopus Importer:2025-04-01
Keywords: ADA-GEL; angiogenesis; biofunctionalization; hydrogel; tissue engineering

Characterization of two different alginate-based bioinks and the influence of melanoma growth within - Schipka, Raphael; Heltmann-Meyer, Stefanie; Schneidereit, Dominik; Friedrich, Oliver; Röder, Jonas; Boccaccini, Aldo R.; Schrüfer, Stefan; Schubert, Dirk W.; Horch, Raymund E.; Boßerhoff, Anja Katrin; Arkudas, Andreas; Kengelbach-Weigand, Annika; et al. (Scientific Reports, 2024)
Extrusion-based bioprinting is an established method in biofabrication. Suitable bioinks have fundamentally different compositions and characteristics, which should be examined, in order to find a perfect model system. Here, we investigate the effect of two alginate-based, yet unalike 3D-printed bioinks, pre-crosslinked alginate-dialdehyde gelatin (ADA-GEL) and a mixture of alginate, hyaluronic acid, and gelatin (Alg/HA/Gel), on the melanoma cell line Mel Im and vice versa in terms of stiffness, shrinkage, cellular behavior and colony formation over 15 days. Rheological stiffness measurements revealed two soft gels with similar storage moduli. The cells did not have a significant impact on the overall stiffness, whereas ADA-GEL (2.5/2.5%) was significantly stiffer than Alg/HA/Gel (0.5/0.1/3%). Regarding the shrinkage of printed constructs, cells had a significant influence, especially in ADA-GEL, which has covalent bonds between the oxidized alginate and gelatin. Multi-photon microscopy exhibited proliferation, cell spreading and migration in ADA-GEL with cell–cell and cell–matrix interaction, dissimilarly to Alg/HA/Gel, in which cells formed spherical, encapsulated colonies. Scanning electron microscopy and histology showed degradation and multi-layered growth on ADA-GEL and fewer examples of escaped cells on Alg/HA/Gel. Both gels serve as proliferation bioink for melanoma with more necrosis in deeper Alg/HA/Gel colonies and differences in spreading and matrix interaction. These findings show the importance of proper characterization of the bioinks for different applications.
CRIS-Team Scopus Importer:2024-06-14
Keywords: 3D-printing; Alginate; Hydrogel; Melanoma; Stiffness

Enhanced vascularization and de novo tissue formation in hydrogels made of engineered RGD-tagged spider silk proteins in the arteriovenous loop model - Steiner, Dominik; Winkler, Sophie; Heltmann-Meyer, Stefanie; Trossmann, Vanessa T.; Fey, Tobias; Scheibel, Thomas; Horch, Raymund E.; Arkudas, Andreas (Biofabrication, 2021)
Due to its low immunogenic potential and the possibility to fine-tune their properties, materials made of recombinant engineered spider silks are promising candidates for tissue engineering applications. However, vascularization of silk-based scaffolds is one critical step for the generation of bioartificial tissues and consequently for clinical application. To circumvent insufficient vascularization, the surgically induced angiogenesis by means of arteriovenous loops (AVL) represents a highly effective methodology. Here, previously established hydrogels consisting of nano-fibrillary recombinant eADF4(C16) were transferred into Teflon isolation chambers and vascularized in the rat AVL model over 4 weeks. To improve vascularization, also RGD-tagged eADF4(C16) hydrogels were implanted in the AVL model over 2 and 4 weeks. Thereafter, the specimen were explanted and analyzed using histology and microcomputed tomography. We were able to confirm biocompatibility and tissue formation over time. Functionalizing eADF4(C16) with RGD-motifs improved hydrogel stability and enhanced vascularization even outperforming other hydrogels, such as fibrin. This study demonstrates that the scaffold ultrastructure as well as biofunctionalization with RGD-motifs are powerful tools to optimize silk-based biomaterials for tissue engineering applications.
CRIS-Team WoS Importer:2021-08-06

Gelatin methacryloyl is a slow degrading material allowing vascularization and long-term use in vivo - Heltmann-Meyer, Stefanie; Steiner, Dominik; Mueller, Claudia; Schneidereit, Dominik; Friedrich, Oliver; Salehi, Sahar; Engel, Felix; Arkudas, Andreas; Horch, Raymund E. (Biomedical Materials, 2021)
In situ tissue engineering is an emerging field aiming at the generation of ready-to-use three-dimensional tissues. One solution to supply a proper vascularization of larger tissues to provide oxygen and nutrients is the arteriovenous loop (AVL) model. However, for this model, suitable scaffold materials are needed that are biocompatible/non-immunogenic, slowly degradable, and allow vascularization. Here, we investigate the suitability of the known gelatin methacryloyl (GelMA)-based hydrogel for in-situ tissue engineering utilizing the AVL model. Rat AVLs are embedded by two layers of GelMA hydrogel in an inert PTFE chamber and implanted in the groin. Constructs were explanted after 2 or 4 weeks and analyzed. For this purpose, gross morphological, histological, and multiphoton microscopic analysis were performed. Immune response was analyzed based on anti-CD68 and anti-CD163 staining of immune cells. The occurrence of matrix degradation was assayed by anti-MMP3 staining. Vascularization was analyzed by anti-alpha-smooth muscle actin staining, multiphoton microscopy, as well as expression analysis of 53 angiogenesis-related proteins utilizing a proteome profiler angiogenesis array kit. Here we show that GelMA hydrogels are stable for at least 4 weeks in the rat AVL model. Furthermore, our data indicate that GelMA hydrogels are biocompatible. Finally, we provide evidence that GelMA hydrogels in the AVL model allow connective tissue formation, as well as vascularization, introducing multiphoton microscopy as a new methodology to visualize neovessel formation originating from the AVL. GelMA is a suitable material for in situ and in vivo TE in the AVL model.
CRIS-Team WoS Importer:2021-09-17

In Vivo Vascularization of Cell-Supplemented Spider Silk-Based Hydrogels in the Arteriovenous Loop Model - Osterloh, Justus; Heltmann-Meyer, Stefanie; Trossmann, Vanessa T.; Cai, Aijia; Kulicke, Yvonne; Terörde, Klara; Sörgel, Celena; Lang, Isabell; Wajant, Harald; Scheibel, Thomas; Fey, Tobias; Steiner, Dominik; et al. (Biomimetics, 2025)
The goal of reconstructive surgery in treating tissue defects is to achieve a stable reconstructive outcome while minimizing donor site morbidity. As a result, tissue engineering has emerged as a key focus in the pursuit of this goal. One approach is to create a tissue container that can be preconditioned and later transplanted into the defect area. The characteristics of the matrices used in the tissue container are critical to this approach’s success. Matrices generated with recombinant, functionalized spider silk (eADF4(C16)-RGD) have been reported to be biocompatible and easy to vascularize. However, the effect of exogenously added proangiogenic cells, such as endothelial cells (T17b), on the vascularization process of matrices generated with this hydrogel in vivo has not been described yet. In this study, we implanted arteriovenous (AV) loop containers filled with a spider silk hydrogel consisting of an eADF4(C16)-RGD matrix and encapsulated, differentiated endothelial T17b cells producing the reporter protein TNFR2-Fc-Flag-GpL. The histological and µCT analyses revealed spontaneous angiogenesis and fibrovascular tissue formation in the container at 2 and 4 weeks post-implantation. The reporter protein was detected after 4 weeks. No severe immune response was observed. Altogether, this study demonstrates that cell-supplemented recombinant spider silk is a highly promising hydrogel to produce matrices for tissue engineering applications.
CRIS-Team Scopus Importer:2025-03-14
Keywords: recombinant spider silk; reconstructive surgery; tissue engineering; vascularization

Recombinant Spider Silk Bioinks for Continuous Protein Release by Encapsulated Producer Cells - Trossmann, Vanessa T.; Heltmann-Meyer, Stefanie; Amouei, Hanna; Wajant, Harald; Horch, Raymund E.; Steiner, Dominik; Scheibel, Thomas (Biomacromolecules, 2022)
Targeted therapies using biopharmaceuticals are of growing clinical importance in disease treatment. Currently, there are several limitations of protein-based therapeutics (biologicals), including suboptimal biodistribution, lack of stability, and systemic side effects. A promising approach to overcoming these limitations could be a therapeutic cell-loaded 3D construct consisting of a suitable matrix component that harbors producer cells continuously secreting the biological of interest. Here, the recombinant spider silk proteins eADF4(C16), eADF4(C16)-RGD, and eADF4(C16)-RGE have been processed together with HEK293 producer cells stably secreting the highly traceable reporter biological TNFR2-Fc-GpL, a fusion protein consisting of the extracellular domain of TNFR2, the Fc domain of human IgG1, and the luciferase of Gaussia princeps as a reporter domain. eADF4(C16) and eADF4(C16)-RGD hydrogels provide structural and mechanical support, promote HEK293 cell growth, and allow fusion protein production by the latter. Bioink-captured HEK293 producer cells continuously release functional TNFR2-Fc-GpL over 14 days. Thus, the combination of biocompatible, printable spider silk bioinks with drug-producing cells is promising for generating implantable 3D constructs for continuous targeted therapy.
CRIS-Team Scopus Importer:2022-09-30

Vessel grafts for tissue engineering revisited—Vessel segments show location-specific vascularization patterns in ex vivo ring assay - Vaghela, Ravikumar; Arkudas, Andreas; Steiner, Dominik; Heltmann-Meyer, Stefanie; Horch, Raymund E.; Hessenauer, Maximilian (Microcirculation, 2021)
Objective: Transplantation of prefabricated tissue-engineered flaps can be a potential alternative for healing large tissue defects. Providing adequate vascular supply for an engineered tissue construct is one of the key points in establishing successful tissue engineering-based treatment approaches. In tissue engineering-based vascularization techniques like the arteriovenous loop, vascular grafts with high angiogenic potential can help to enhance neovascularization and tissue formation. Therefore, our study aimed to compare the angiogenic potential of vascular grafts from different locations in the rat. Methods: The angiogenic activity was investigated by an ex vivo vessel outgrowth ring assay using 1-mm height vascular segments embedded in fibrin for 2 weeks. Results: Maximum vessel outgrowth was observed on Days 10–12. Upper extremity vessels exhibited stronger outgrowth than lower extremity vessels. Moreover, arterial vessels demonstrated higher angiogenic potential compared with venous vessels. Conclusion: Collectively, our ex vivo findings suggest that upper extremity arterial vessels have a higher angiogenic capacity, which could be used to improve neovascularization and tissue formation in tissue engineering.
CRIS-Team Scopus Importer:2021-12-17
Keywords: AV-loop; reconstructive surgery; tissue engineering; vascularization; vessel network